THE EFFECT OF WORKPLACE QUALITY AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE’S PRODUCTIVITY (CASE STUDY: CV. KOMBOS MANADO) - Emor, Desinta; Kindangen, Paulus; Worang, Frederik G. (Universitas Sam Ratulangi, 2017)
Abstract: In global era, every organization seeks to improve employee’s performance to create productive employees as their asset. The aim of this study to determine the effect of workplace quality and organizational commitment on employee’s productivity. In this study, population refers to the employees of CV. Kombos Manado by using saturation sampling technique and sample size of 40 respondents through questionnaires. The result of data processed using SPSS 24 shows all the variables of workplace quality and organizational commitment simultaneously effect on employee’s productivity in CV Kombos Manado. As for partially, workplace quality does not have significant effect on employee’s productivity in CV. Kombos Manado, whereas organizational commitment have significant effect on employee’s productivity in CV. Kombos Manado. CV. Kombos Manado should consider about the importance of the effect of workplace quality and organizational commitment in the company. Because according to the result of this study, those two factors have an effect through the employee’s productivity. And also, company should make more activities to improve the employee’s feel of connect with the company.Keywords: Workplace Quality, Organizational Commitment, Employee’s Productivity